The Principal's Strategy in Improving Teachers' Teaching Motivation at MA Al Huda Tulung Balak - Siti Maryamah; Mispani Mispani; Choirudin Choirudin (Assyfa Journal of Islamic Studies, 2026)
This study aims to analyze the principal's strategies in improving teachers' teaching motivation, their impact on teacher performance, and the challenges faced in implementation. The research employed a qualitative approach with a case study design at MA Al Huda Tulung Balak, East Lampung. Data were collected through participant observation, in-depth interviews with 8 informants (principal, 6 teachers, and 1 administrative staff), and document study. Data analysis used the Miles and Huberman model. The findings reveal that the principal implemented seven holistic and integrative strategies: (1) humanistic and reflective clinical supervision, (2) spiritual and professional value-based motivation, (3) sustainable capacity development through training, (4) proportional reward and punishment system, (5) conducive work environment engineering, (6) participatory and transformational leadership style, and (7) mobilization of parental and community support. The impacts include increased teaching innovation (teachers using varied methods rose from 40% to 75%), participation in professional development (90%), administrative discipline (from 65% to 85%), and technology utilization (from 30% to 55%). Challenges include limited infrastructure, weak external support, teacher competency heterogeneity, the principal's heavy workload, and low internal drive among a small portion of teachers. This study confirms Maslow's Hierarchy of Needs Theory, Deci and Ryan's Self-Determination Theory, and Bass's Transformational Leadership Theory in the context of pesantren-based rural private madrasahs.